Prevalence of Thyroid Nodules in China: A Health Examination Cohort-Based Study - Li, Yunhai; Jin, Cheng; Li, Jie; Tong, Mingkun; Wang, Mengxue; Huang, Jiefeng; Ning, Yi; Ren, Guosheng (Frontiers in Endocrinology, 2021)
Background: Thyroid nodules are a common clinical problem and some are potentially cancerous; however, little is known about the prevalence of thyroid nodules in China. The objective of this study was to investigate the prevalence of thyroid nodules in a healthy Chinese population. Methods: We reviewed electronic medical records of 13,178,313 participants from 30 provinces and regions who received health examinations and underwent thyroid ultrasound at Meinian Onehealth Healthcare in 2017. Among them, 6,192,357 were excluded based on predefined criteria. All thyroid nodules were diagnosed by ultrasonography, and standardized protocols were adopted for data collection, quality control, and data management. Results: A total of 6,985,956 participants (mean age: 42.1 ± 13.1 years) were included in this study. The overall prevalence of thyroid nodules was 36.9% (95% CI, 35.7%–38.1%; age- and sex-standardized prevalence 38.0% [95% CI, 37.0%–39.1%]). The prevalence of thyroid nodules in females (44.7% [95% CI, 43.4%–45.9%], age-standardized prevalence: 45.2% [95% CI, 44.1%–46.4%]) was significantly higher than that in males (29.9% [95% CI, 28.8%–31.0%], age-standardized prevalence 31.2% [95% CI, 30.1%–32.2%]; P < 0.001). The prevalence of thyroid nodules decreased from <18 to 25 years, while increased with age over 25 years old. The top three provinces with the highest prevalence of thyroid nodules were Jilin (47.6%), Liaoning (44.8%), and Shandong (43.9%), whereas Guizhou (23.9%), Chongqing (26.2%), and Shaanxi (26.4%) had the lowest prevalence. Females had more than 10% higher rates of thyroid nodules than males in all included provinces and regions, except for Tianjin (8.0%). Based on the geographical regions of China, the northeast had the highest prevalence (46.8% [95% CI, 44.1%–49.2%]), whereas northwest had the lowest prevalence (28.9% [95% CI, 26.9%–31.6%]. Based on multivariable logistic regression analysis, factors including age, gender, body mass index, systolic blood pressure, diastolic blood pressure, uric acid, fasting blood glucose, triglycerides, high-density lipoproteins, and low-density lipoproteins were significantly associated with the presence of thyroid nodules. Conclusion: This study provides the first nationwide analysis of the prevalence of thyroid nodules in China. Our results showed that the prevalence of thyroid nodules was high in health screening Chinese people with regional-specific patterns.